Analisis Kelayakan Pasar Tahu Produksi Polinela - Bina Unteawati; Fitriani Fitriani (Jurnal Ilmiah ESAI, 2007)
This research was due to know which Polinela tofu production was feasible in marketing aspect or not.  The marketing aspect describes market condition including the potential market, market segmentation, marketing target and market opportunity.  The analysis approached by quantitative and qualitative  descriptive methode.  Based on the marketing analysis, Polinela tofu was feasible at potensial market, marketing target, and market segmented. Kata Kunci:   kelayakan pasar,  potensi pasar, sasaran, dan segmentasi pasar.